Analisa dan Perancangan Chatbot Menggunakan Metode Extreme Programming untuk Memberikan Informasi Penjualan PT. Megalestari Epack Sentosaraya Tbk. - Ahmad Fikriyadi; Diki Purnomo Aji; Fathurrahman; Himmatul Ulya Al Makassari; Aries Saifudin (Journal of Research and Publication Innovation, 2023)
Internet use in Indonesia is increasing from year to year. Entering the Revolutionary Era 4.0, technological developments have become fast, on the other side artificial intelligence (AI) is used to assist current jobs. Sales at PT. Megalestari Epack Sentosaraya Tbk. have their own problemsÂ in replying to chats and emails from many customers, so to overcome this problem a chatbot will be used to provide sales information that is usually conveyed by sales. So that the sales will focus on â€œsalesâ€ and no longer reply to customer chats. The method used in this research is the extreme programming method, in which the software development methodology is used to improve quality and respond quickly if there is an urgent customer need. Extreme programming method has four stages, among others are planning, designing, coding, and testing, however coding and testing will be carried out in further research. The results of this study are system requirements represented in use case diagrams and flowcharts and the system modeling used is the Unified Modeling Language (UML). Â